Physicomechanical and magnetic properties of neoprene based rubber ferrite composites - Prema, K. H.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Polymer-Plastics Technology and Engineering, 2008)
Fine (approximately 18nm) particles of nickel ferrite were synthesized by the sol-gel technique, and their structural properties were evaluated by X-ray diffraction. Neoprene-based rubber ferrite composites were prepared by incorporating these nickel ferrite powders in the rubber matrix according to a specific recipe. The cure characteristics were analyzed, and the samples were molded into particular shapes whose properties were determined according to ASTM standards. Magnetization studies were carried out using a Vibrating Sample Magnetometer. This study indicates that neoprene rubber-based flexible magnets with desired magnetic properties and appropriate mechanical properties can be prepared by incorporating an adequate amount of nanoscale nickel ferrite particles within the rubber matrix.
Keywords: Ferrite; ferrite composites; flexible magnets; neoprene rubber; rubber; Sol-gel method